The Relationship Between Nurse’s Professional Quality of Life, Mindfulness, and Hardiness: A Cross-Sectional Study During the COVID-19 Outbreak - Zakeri, Mohammad Ali; Ghaedi-Heidari, Fatemeh; Khaloobagheri, Elham; Hossini Rafsanjanipoor, Sayed Mortaza; Ganjeh, Hamid; Pakdaman, Hassan; Abbasifard, Mitra; Mehdizadeh, Mehdi; Zakeri Bazmandeh, Abbas; Dehghan, Mahlagha (Frontiers in Psychology, 2022)
In the pandemic of COVID-19 disease, various factors can affect the occupational status of nurses. This study aimed to assess the evaluation of the relationship between nurse’s professional quality of life, mindfulness and hardiness during the outbreak of COVID-19. Methods: This cross-sectional study included 239 nurses from two medical centers in Rafsanjan, Iran. Quota sampling was performed from August to November 2020. A demographic form, the Professional Quality of Life Scale (ProQOL), the Freiburg Mindfulness Questionnaire_ Short Form (FMI-SF), and the Occupational Hardiness Questionnaire (OHQ) were used to collect data. Results: Compassion satisfaction, secondary traumatic stress, and burnout were all moderate among nurses. Hardiness was the best predictor of compassion satisfaction. Mindfulness was the best predictor of both secondary traumatic stress and burnout. Psychological hardiness and mindfulness had the greatest impact on nurses' quality of professional life during the COVID-19 pandemic. Conclusion: Therefore, in order to improve nurses' quality of professional life, psychological hardiness and mindfulness, necessary psychological programs and interventions should be designed and implemented.